Bifluorene Single Crystals with Extremely Low‐Threshold Amplified Spontaneous Emission. Issue 5 (27th December 2016) - Kreiza, Gediminas; Baronas, Paulius; Radiunas, Edvinas; Adomėnas, Povilas; Adomėnienė, Ona; Kazlauskas, Karolis; Ribierre, Jean‐Charles; Adachi, Chihaya; Juršėnas, Saulius
Abstract : Organic single crystals offering numerous advantages due to their long‐range molecular order are considered a promising gain medium for realization of electrically‐pumped organic lasers provided their amplified spontaneous emission (ASE) threshold is sufficiently low. Unfortunately, ASE thresholds of such crystals are typically more than one order of magnitude higher (in the range of tens of kW cm −2 ) as compared to those of amorphous neat/doped films. Here, this issue is addressed by rationally designing bifluorene‐based compounds to express weak intermolecular coupling in the crystalline phase. The twisted molecular backbone as well as out‐of‐plane twisted dimethyl moieties attached at the fluorene end‐groups additionally benefit with enhanced electron–vibronic coupling resulting in a large Stokes shift (0.5 eV) and reduced reabsorption of emission. Endowed with such features the bifluorenes exhibit similarly high radiative decay rates (≈1.5 × 10 9 s −1 ) when doped in polystyrene matrix at low concentrations and in sublimation‐grown single crystals. The high radiative rates accompanied by excellent waveguiding properties, favorable orientation of transition dipole moments as well as non‐overlapping excited‐state absorption and gain regions enable achieving extremely low ASE thresholds (≈700 W cm −2 ) in the bifluorene single crystals. The achieved low threshold encourages employment of rationally designed molecules in organic crystals for lasing applications. Abstract : An extremely low amplified spontaneous emission threshold (700 W cm −2 ) is reported in sublimation‐grown single crystals of bifluorene compounds. Such low thresholds are found to originate from high radiative rates (1.5 × 10 9 s −1 ), absence of excited‐state absorption in the gain region, and favorable orientation of transition dipole moments accompanied by excellent waveguiding properties of the single crystals.